The Influence of CAT and Self-Disclosure on the Classroom - Turk, Caroline I. (My University, 2023)
Classroom relational dynamics influence the ability to teach and learn effectively, making positive, meaningful relationships in the classroom crucial. Communication Accommodation Theory (CAT) explores how communicative adjustments, or accommodations, “reflect and affect personal and social relationships” (Soliz et al., 2021, p. 130). Thus, implementing CAT in the classroom could result in greater effectiveness of teaching and learning. Because CAT is used tomanage identity and relationships, it is also important to understand the results of communicating identity in the classroom. Communicating identity by self-disclosing can foster a connected classroom dynamic (Johnson & LaBelle, 2015), resulting in greater satisfaction with and appreciation of classroom relationships (Hosek, 2015). Because CAT, specifically accommodation behaviors and self-disclosure, influences academic performance and relational satisfaction, their usage in classrooms would bolster instructional communication. To understand the influence of CAT and self-disclosure on the classroom, a thorough literature review examining research on CAT’s classroom influence will be conducted first.Then, the implementation of self-disclosure in the classroom will be analyzed. Together, these two parts will explain the importance of CAT and self-disclosure’s usage in classrooms to increase instructional effectiveness and build positive relationships.